The intlectual dimension of Pedro Manterola - Matute, Emilio (Huarte de San Juan. Geografía e Historia, 2016)
Pedro Manterola Armisen has been one of the most outstanding figures from the cultural panorama in Navarra in the last fifty years due to the importance of his intellectual work in the diverse fields that caracterize the artistic work such as paintor, professor, lecturer, art critic, writer, president and director of the Fundación Museo Jorge Oteiza and Director of the Cathedra on Jorge Oteiza.
Keywords: Manterola; Navarre; painter; writer; teacher; art critic; lectur